Ultrasound evaluation of digital flexor tendons of jumping horses undergoing treadmill training - Buzzetti, Ananda Parra (2022)
This study aimed to perform ultrasonographic evaluation of the digital flexor tendons of jumping horses undergoing complementary training on a treadmill. Fifteen Brazilian Sport horses were divided into two groups: Group I with 7 animals in physical training complementary to the standard training at the Brazilian Army’s Riding School; and Group II with 8 animals in standard training used in the Brazilian Army’s Riding School. Complementary training was performed on a treadmill on an inclined plane. Ultrasonographic images were taken at the beginning and at the end of training. The left thoracic and pelvic limbs of horses were evaluated for echogenicity values and cross-sectional areas of the superficial digital flexor tendons (SDFTs) and deep digital flexor tendons (DDFTs) in zones IA, IIB, and IIIB. The mean areas of the SDFT were 93.7 mm2 and 95.8 mm2 at the beginning and the end of training, respectively. The cross-sectional area of DDFT increased from 124.6 mm2 at the beginning of training to 136.8 mm2 at the end of training. The echogenicity values of both tendons were between 0 and 1 as expected, concluding that clinically, the animals showed adaptation to the exercise protocol with no signs of tendon injury being detected, implying that traditional training and complementary training are safe.